Effects of the Zbtb1 Gene on Chromatin Spatial Structure and Lymphatic Development: Combined Analysis of Hi-C, ATAC-Seq and RNA-Seq - Wang, Junhong; Shi, Chunwei; Cheng, Mingyang; Lu, Yiyuan; Zhang, Xiaoyu; Li, Fengdi; Sun, Yu; Li, Xiaoxu; Li, Xinyang; Zeng, Yan; Wang, Chunfeng; Cao, Xin (Frontiers in Cell and Developmental Biology, 2022)
Zbtb1 (zinc finger and BTB domain containing 1) is a member of mammalian zbtb gene family. A series of bioinformatics analysis was carried out for the EL4 cell and the Zbtb1-deficient EL4 cell by Hi-C, ATAC-seq and RNA-seq techniques. Finally, Hi-C results showed that the intensity of chromatin interaction in the deletion group decreased with distance, the degree of chromosome interaction decreased significantly, the AB division region changed significantly, and the compactness of TAD structure decreased; The results of ATAC-seq showed that the open area and degree of chromatin in the deletion group decreased; 7778 differentially expressed mRNAs were found by RNA-seq. Our experimental results for the first time expounded the significance of zbtb1 gene for T cell development, lymphocyte production and apoptosis from the aspects of chromosome spatial structure and chromatin opening degree, and provided relevant theoretical basis and data support for the in-depth study of related zbtb1 genes in the future.